2019
DOI: 10.1021/acs.langmuir.9b00483
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Aqueous and Binary Mixture Drops on Lubricating Fluid-Coated Slippery Surfaces

Abstract: The mobility of liquid drops on lubricant-infused slippery surfaces depends strongly on various system parameters, for example, surface energy and roughness of the underlying solid surface and surface tension and viscosity of the test and the lubricating fluids. Here, we investigate lubricant-coated slippery surfaces fabricated on smooth hydrophobic solid surfaces and examine the influence of thickness and viscosity of the lubricating oil on the velocity of aqueous drops. We also investigate the effect of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…3.a and 3.c. Interestingly, in spite of much higher static viscosities, the average speed of PAA 10 drops with concentration somewhat below 2500 ppm is also comparable to that of glycerol/water drops, within the uncertainty related to the fact that the curves refer to different surfaces which may present slightly different lubricant thicknesses 41,42 . This result can be rationalized assuming that the effective viscosity of the moving PAA 10 drops is much lower due to the nite shear rate.…”
Section: Resultsmentioning
confidence: 74%
“…3.a and 3.c. Interestingly, in spite of much higher static viscosities, the average speed of PAA 10 drops with concentration somewhat below 2500 ppm is also comparable to that of glycerol/water drops, within the uncertainty related to the fact that the curves refer to different surfaces which may present slightly different lubricant thicknesses 41,42 . This result can be rationalized assuming that the effective viscosity of the moving PAA 10 drops is much lower due to the nite shear rate.…”
Section: Resultsmentioning
confidence: 74%
“…31 In equilibrium, balancing the viscous stress on either side of the interface provides 32 In our experiment, μ D ≪ μ O , and the above scaling relation can be reduced to V i ≈ Vμ D h/μ O R. When it integrates over a surface area of order R 2 , we get the viscous stress in a droplet which scales as μ D V/R, which demonstrates that the dissipation in the droplet is due to the change in the droplet base radius induced by the change of the surface tension of the droplet. The viscous force in the droplet (F D ) scales as 33 F VR…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Low shedding rate of droplets can affect the efficiency through clogging of the openings of meshes. The main approach to maximize the shedding rate is to add coatings (mainly hydrophobic) to the meshes which can reduce the contact angle hysteresis of the droplets that attach to the surface, and therefore, facilitate their drainage [13,14]. In a recent study, Shi et al [15] have shown that removing the horizontal wires and only using the vertical array of wires on meshes (called harps), can be an effective way to increase the shedding rate of fog droplets to avoid clogging, and therefore, enhancing the efficiency of the collector.…”
Section: Introductionmentioning
confidence: 99%